Novel Biodegradable and Biocompatible Poly(3-hydroxyoctanoate)/Bacterial Cellulose Composites - Basnett, Pooja; Knowles, Jonathan C.; Pishbin, Fatemah; Smith, Caroline; Keshavarz, Tajalli; Boccaccini, Aldo R.; Roy, Ipsita (Advanced Engineering Materials, 2012)
Novel poly(3-hydroxyoctanoate), P(3HO), and bacterial cellulose composites have been developed. P(3HO) is hydrophobic in nature whereas bacterial cellulose is extremely hydrophilic in nature. Therefore, homogenized bacterial cellulose has been chemically modified in order to achieve compatibility with the P(3HO) matrix. Modified bacterial cellulose microcrystals and P(3HO) have been physically blended and solvent casted into two-dimensional composite films. Mechanical characterization shows that the Young's modulus of the P(3HO)/bacterial cellulose composites is significantly higher in comparison to the neat P(3HO) film. The melting temperature (T m) of the composites is lower while the glass transition temperature (T g) is higher than the neat P(3HO) film. Also, the composite film has a rougher surface topography as compared to the neat P(3HO) film. A month's in vitro degradation study has been carried out in Dulbeccos modified eagle medium and in phosphate buffer saline. The incorporation of modified bacterial cellulose microcrystal in the P(3HO) film has increased the degradability of the composite film. Finally, in vitro biocompatibility studies using human microvascular endothelial cells established the biocompatibility of the P(3HO)/bacterial cellulose microcrystal films. The cell proliferation was 50-110% higher on the P(3HO)/bacterial cellulose composites as compared to the neat P(3HO) film. Hence, in this study, for the first time, P(3HO)/bacterial cellulose composites have been developed. The addition of bacterial cellulose has resulted in properties that are highly desirable for medical applications including the development of biodegradable stents. Novel P(3HO)/bacterial cellulose composites have been developed to be used as a potential material for a range of medical applications including the development of biodegradable stents. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.novelb